2020
DOI: 10.1111/nicc.12525
|View full text |Cite
|
Sign up to set email alerts
|

The effects of noise levels on pain, anxiety, and sleep in patients

Abstract: Background Intensive care is a noisy environment for patients and one that affects pain, anxiety levels, and sleep quality. Aims and objectives To determine the relationship between noise levels and pain, anxiety, and sleep levels in patients in intensive care units. Design A descriptive and observational study design was used. Methods This study was conducted between June and December 2018 in a public hospital and included 111 patients admitted to surgical critical care for at least 24 hours. Three Benetech G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…This semistructured form was established by the investigators after some literature review [4,5,13]. The form consisted of 13 questions on the sociodemographic features and medical status of the patients.…”
Section: Subject Descriptive Characteristics Formmentioning
confidence: 99%
See 1 more Smart Citation
“…This semistructured form was established by the investigators after some literature review [4,5,13]. The form consisted of 13 questions on the sociodemographic features and medical status of the patients.…”
Section: Subject Descriptive Characteristics Formmentioning
confidence: 99%
“…Loud noise has negative effects on the sleep process such as difficulty in falling asleep, frequently waking up, and decreased sleep quality and also causes psychological effects such as stress, instability, aggression, mood changes, and anxiety [2,3]. It has been shown in many studies that disturbing noise in the hospital environment causes sleep problems in patients [4,5], and it has been reported that there is a relationship between the noise levels and anxiety [5].…”
mentioning
confidence: 99%
“…On the other side, logistic facilities tend to favor hospital conditions. Admittedly, they can create stressful conditions for people not being used to being hospitalized ( 65 ). But they also offer easy access to EEG, the only way to measure objective sleepiness, and perfectly controlled conditions: the participants are treated equally, have their meal at the same time, and their sleep the night before the medical test is controlled.…”
Section: Guidelinesmentioning
confidence: 99%
“…Identifying risk factors that are modifiable in hospital, or upon returning home could further reduce the incidence, duration or severity of PICS. Future research can explore further the patient experience (be it the ICU environment, interactions with staff and co‐patients, or visits from loved ones) 16‐18 and how this can be improved to reduce psychological complications. The ABCDEF bundle demonstrates how known modifiable risk factors can be targeted to ameliorate PICS/PICS‐p, in this case by reducing delirium and immobility to prevent cognitive impairment and neuromuscular weakness 10,19 …”
Section: Modifiable Factorsmentioning
confidence: 99%